Lapd '53 - Ellroy, James; Martin, Glynn (Abrams, Inc, 2015)
A remarkable portrait of "true L.A.noir" with archival photos from the Los Angeles Police Museum and text by legendary crime writer James Ellroy ( Los Angeles Times ).  James Ellroy, the undisputed master of crime writing, has teamed up with the Los Angeles Police Museum to present a stunning text on 1953 L.A.